1990
DOI: 10.1128/mcb.10.11.6013
|View full text |Cite
|
Sign up to set email alerts
|

Human P450scc gene transcription is induced by cyclic AMP and repressed by 12-O-tetradecanoylphorbol-13-acetate and A23187 through independent cis elements.

Abstract: Long-term regulation of mammalian steroid hormone synthesis occurs principally by transcriptional regulation of the gene for the rate-limiting cholesterol side-chain cleavage enzyme P450scc. Adrenal steroidogenesis is regulated primarily by two hormones: adrenocorticotropin, which works via cyclic AMP (cAMP) and protein kinase A, and angiotensin H, which works via Ca2+ and protein kinase C. Forskolin and 8-bromo-cAMP stimulated, while prolonged treatment with a phorbol ester (12-O-tetradecanoylphorbol-13-aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 35 publications
5
48
1
Order By: Relevance
“…Preliminary studies on the 5Ј-flanking region of the gene demonstrated the ability of a 2.5-kb 1 DNA fragment to confer basal and cAMP responsive activity when transiently transfected into mouse adrenal Y1 tumor cells (11)(12)(13). Subsequent studies in mouse Leydig MA-10 (14), I-10 (15), human placenta JEG-3 (16), and adrenal NCI-H295 (17) cells identified regions of the 5Ј-flanking DNA that conferred basal promoter activity and response to cAMP.…”
mentioning
confidence: 99%
“…Preliminary studies on the 5Ј-flanking region of the gene demonstrated the ability of a 2.5-kb 1 DNA fragment to confer basal and cAMP responsive activity when transiently transfected into mouse adrenal Y1 tumor cells (11)(12)(13). Subsequent studies in mouse Leydig MA-10 (14), I-10 (15), human placenta JEG-3 (16), and adrenal NCI-H295 (17) cells identified regions of the 5Ј-flanking DNA that conferred basal promoter activity and response to cAMP.…”
mentioning
confidence: 99%
“…The sequence of nucleotides -118 to -83 (CRS) for the bovine CYPllA gene has been shown to enhance the transcription of the gene in response to cAMP [15], while the sequence of nucleotides -325 to -34 in the mouse CYPIIA gene [13] contains several DNA elements, including the tissue-specific-factor-binding site (SFl), which were required for sufficient CAMP responsiveness. Moore and co-workers [17] reported that the nucleotides -152 to -89 were necessary for basal expression, but not for cAMP responsiveness, of the human CYPllAl gene in Y-1 cells [17], while the region composed of nucleotides -108 to -89 was needed for induction in response to forskolin treatment in human JEG-3 choriocarcinoma cells [34]. On the basis of these reports, Momoi and co-workers [ 181 discussed that regions including the bovine CRS, mouse SF-3 and the human nucleotides -152 to -89 were important for the transcription of the CYPllAl gene in these animal species [I 81.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, human CYP17 and CYP21A2 genes have been demonstrated to be controlled by CREB or its related factors through binding to the DNA elements 111, 121, although they do not have a typical CRE consensus sequence. Regulatory mechanisms of CYPllAl expression have been investigated with mouse, rat, bovine, sheep and human genes [13][14][15][16][17][18] 331. In the bovine CYPllA gene [15, 181, a cis regulatory region was localized between nucleotides -118 and -83, and Spl and adrenal-specific protein Correspondence to Y. Fujii-lriyama,…”
mentioning
confidence: 99%
“…Phospholipids failed to impair the forskolin-triggered increase in progesterone synthesis as opposed to LH-stimulated progesterone production, suggesting that postreceptor cAMP signalling is little affected by these lipids. Long-term regulation of mammalian steroid hormone synthesis occurs principally by transcriptional regulation of the gene for the rate-limiting cholesterol side-chain cleavage enzyme P450 scc (Moore et al 1990). Its expression is positively regulated via the cAMP-PKA pathway; negative regulation includes elevation of the intracellular free Ca 2+ level (Moore et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of follicular progesterone synthesis is brought about via numerous pathways. The preovulatory LH surge elevates the progesterone level of the follicular fluid mainly through a cAMP-protein kinase A (PKA) signalling towards nuclear steroidogenic transcription factors that stimulate expression of thecal and granulosal steroidogenic enzymes (Moore et al 1990, Mamluk et al 1998.…”
Section: Introductionmentioning
confidence: 99%